IMPACT COVID-19: INFLATION ON STAPLE FOOD, UNEMPLOYMENT, THEFT, MARIJUANA CASES IN JAYAPURA CITY IN 2020-2021 - Marlina Flassy; Ferinandus Leonardo Snanfi (Universitas Padjadjaran, 2022)
This study aims to investigate how the impact of COVID-19 to the inflation of staple foods, increasing in unemployment 2,956 people, theft 2,940 cases and marijuana 50 cases in Jayapura City in 2020. To analyze the problem in this study, Thomas R. Dye Policy Theory was used. Qualitative research method was used. Research location is in Jayapura city in 2020-2021. There are 20 respondents gathered in this study: 1 respondent of Head of Health Department of Jayapura city; 1 respondent of Head of Department of Industry, Trade, Cooperatives and SMEs of Jayapura city; 1 respondent of Head of Department of Labor of Jayapura city; 2 respondents of Head of Detective for Theft and Marijuana Cases; 5 respondents of private employees; 6 respondents of neighborhood chiefs and respected figures in society; and 4 respondents of high school students and university students. The data collected and analyze from interview, observation and documentation according to the reality. In Jayapura City in 2021, the impact of COVID-19 still increase, the rise of staple food, the number of unemployment to 12,788 people, theft cases to 3,920 cases and marijuana cases to 60 cases. The suggestions to Mayor of Jayapura City in 2022 are lower monthly and yearly tax for malls, shops, hotels, traditional markets, give the donations or helps entrepreneurs suffering financial problems, no termination of employees in private sectors, ease the approval of business license issues and also invite the big investor to come and open the new business in Jayapura City.